Impact of Leadership Styles on Organizational Culture of the Power Sector of Himachal Pradesh - Sood, Ina; Dey, Prajna Paromita; Saha, Shantanu (Prabandhan: Indian Journal of Management, 2019)
The role of leadership has gained a great deal of attention in the present unpredictable environment with intense competition. This study examined the effect of leadership on organizational culture as development of the culture of an organization is interwoven with the development of its leaders. The study also examined the impact of demographic variables, particularly age and work experience, on these factors as organizations comprise of employees of different age groups, and both experienced employees and freshers equally strive for the accomplishment of the goals, and hence, need to be managed effectively. Perceptions of 221 managers were collected from three different electricity departments of Himachal Pradesh on leadership style and organizational culture. The results showed statistically significant differences across the demographic variables in relation to leadership styles and organizational culture. The study also found strong positive relation between leadership (both transactional and transformational) and organizational culture. Since all three leadership styles were found to impact organizational culture, organizations need to find the best fit leadership style in order to obtain the desired organizational culture.